Glycan Microarrays as Chemical Tools for Identifying Glycan Recognition by Immune Proteins - Gao, Chao; Wei, Mohui; McKitrick, Tanya R.; McQuillan, Alyssa M.; Heimburg-Molinaro, Jamie; Cummings, Richard D. (Frontiers in Chemistry, 2019)
Glycans and glycan binding proteins (GBPs or lectins) are essential components in almost every aspect of immunology. Investigations of the interactions between glycans and GBPs have greatly advanced our understanding of the molecular basis of these fundamental immunological processes. In order to better study the glycan-GBP interactions, microscope glass slide-based glycan microarrays were conceived and proved to be an incredibly useful and successful tool. A variety of methods have been developed to better present the glycans so that they mimic natural presentations. Breakthroughs in chemical biology approaches have also made available glycans with sophisticated structures that were considered practically impossible just a few decade ago. Glycan microarrays provide a wealth of valuable information in immunological studies. They allow for discovery of detailed glycan binding preferences or novel binding epitopes of known endogenous immune receptors, which can potentially lead to the discovery of natural ligands that carry the glycans. Glycan microarrays also serve as a platform to discover new GBPs that are vital to the process of infection and invasion by microorganisms. This review summarizes the construction strategies and the immunological applications of glycan microarrays, particularly focused on those with the most comprehensive sets of glycan structures. We also review new methods and technologies that have evolved. We believe that glycan microarrays will continue to benefit the growing research community with various interests in the field of immunology.